Trio exome sequencing identifies de novo variants in novel candidate genes in 19.62% of CAKUT families - Merz, Lea Maria; Kolvenbach, Caroline M.; Wang, Chunyan; Mertens, Nils David; Seltzsam, Steve; Mansour, Bshara; Zheng, Bixia; Schneider, Sophia; Schierbaum, Luca; Hölzel, Selina; Salmanullah, Daanya; Pantel, Dalia; et al. (Genetics in medicine, 2025)
Purpose - Congenital anomalies of the kidney and urinary tract (CAKUT) encompass heterogenous malformations arising from defective nephrogenesis. To date, approximately 50 monogenic genes are known to cause CAKUT if mutated. Recent studies show the impact of de novo variants in genetic disease etiology. Trio exome sequencing identifies de novo variants in novel candidate genes in 19.62% of CAKUT families. - Methods - We performed trio-based exome sequencing in 209 families with CAKUT to detect novel candidate disease genes. - Results - Trio analysis yielded in the identification of CAKUT candidate genes in 96 of 209 trio families (45.93%). In 41 of 209 cases, we detected strong de novo variants in 45 potential novel CAKUT candidate genes (19.62%). We developed a prioritization approach that highlights a truncating de novo variant in SOX13 (HGNC:11192) as a promising cause for CAKUT. In addition, further allele carriers for the candidate gene CHD1L (HGNC:1916) were identified, thus supporting the role of CHD1L in the pathogenesis of CAKUT. - Conclusion - We conclude that de novo variants in potential novel CAKUT candidate genes contribute to the disease etiology and present SOX13 as a potential novel cause for CAKUT.
Online verfügbar: 11. April 2025, Artikelversion: 5. Juni 2025
Gesehen am 19.01.2026